2002
DOI: 10.1002/mpo.10055
|View full text |Cite
|
Sign up to set email alerts
|

CNS late‐effects after ALL therapy in childhood. Part III: Neuropsychological performance in long‐term survivors of childhood ALL: Impairments of concentration, attention, and memory*†‡

Abstract: Cranial irradiation in combination with MTX therapy was associated with deficits in attention, concentration, and the ability of sequencing and processing, measured by the Kaufman factor Freedom from Distractibility. Our results support the strategy of avoiding prophylactic CNS irradiation in low risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 51 publications
8
106
0
6
Order By: Relevance
“…However, an internal comparison did not reach significance, which could be due to the analyses being based on small numbers in relation to this rather infrequent event. The finding that male survivors of CNS tumours had a reduced chance of completing basic education probably reflects the well-known risk for neuropsychological sequelae after cranial radiotherapy (Lannering et al, 1990;Jankovic et al, 1994;Langer et al, 2002;Reimers et al, 2003) and the subsequent learning difficulties, which cannot be compensated fully by special educational programmes (Peckham, 1991;Haupt et al, 1994;Dongen-Melman et al, 1997;Mitby et al, 2003). The finding that female survivors of CNS tumours had a reduced chance of attaining education at most levels may support the suggestion that the developing female brain is more vulnerable to cranial radiation (Schlieper et al, 1989;Bleyer et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
“…However, an internal comparison did not reach significance, which could be due to the analyses being based on small numbers in relation to this rather infrequent event. The finding that male survivors of CNS tumours had a reduced chance of completing basic education probably reflects the well-known risk for neuropsychological sequelae after cranial radiotherapy (Lannering et al, 1990;Jankovic et al, 1994;Langer et al, 2002;Reimers et al, 2003) and the subsequent learning difficulties, which cannot be compensated fully by special educational programmes (Peckham, 1991;Haupt et al, 1994;Dongen-Melman et al, 1997;Mitby et al, 2003). The finding that female survivors of CNS tumours had a reduced chance of attaining education at most levels may support the suggestion that the developing female brain is more vulnerable to cranial radiation (Schlieper et al, 1989;Bleyer et al, 1990).…”
Section: Discussionmentioning
confidence: 83%
“…22 However, in a larger study of 121 patients with ALL, cumulative IT dose did not predict cognitive functioning. 23 Among all children who participated in the randomized, controlled study (N ϭ 1,018), grades 3 to 4 CNS toxicity on therapy, as reported by treating physicians, occurred in 5.8% on IT methotrexate and in 6.7% of those on triple IT therapy. 8 In our cross-sectional sample, parents of patients reported a higher frequency of acute CNS toxic events of any severity during therapy in the IT methotrexate group.…”
Section: ‫ء‬mentioning
confidence: 99%
“…Th e authors of clinical studies indicate that females have a higher risk of neurocognitive complications aft er therapy ALL [26][27][28], which was not the case in this study-complications were equally represented and in male and female patients. According to the results of other authors, dexamethasone more often causes psychiatric disorders compared to prednisone, primarily due to the greater liposolubility which increased the crossing of blood-brain barrier [29].…”
Section: Discussionmentioning
confidence: 47%